Hydrodynamic drag of small sea kayaks - Lazauskas, L.; Winters, J. (1997)
The total calm-water resistance (wave plus viscous) of four popular single seat sea kayaks is calculated and compared with experimental results. Michell's integral is used for the wave resistance, the 1957 ITTC line for the skin friction, and a simple empirical formula for the form drag. The agreement of the predicted drag with experiment is generally very good, especially at the lower speeds considered in the present note. At higher speeds, discrepancies are probably due to sinkage and trim effects which are not accounted for in the mathematical model.